Analysis of Adulterated Pangasius Hypopthalmus Oil by ATR-FTIR Spectroscopy and Chemometric - Lisa Andina; Revita Saputri; Aristha Novyra Putri; Endang Lukitaningsih; Abdul Rohman (Journal of Food and Pharmaceutical Sciences, 2019)
In this recent study, ATR-FTIR spectroscopy and chemometrics have been successfully used for theclassification and quantitative analysis of adulterated Pangasius Hypopthalmus (P. hypopthalmus) oil. The aimof this research was to evaluate the ability of ATR-FTIR spectroscopy and chemometric to perform theclassification and quantitative analysis of adulterated P. hypopthalmus oil in a binary mixture with palm oil(PO) and coconut oil (CO). In the development of FTIR spectroscopy combined with chemometrics for theclassification and quantitative analysis of P. hypopthalmus oil, P. hypopthalmus oil (MP and LFP) mixed withother oils such as coconut oil (CO) and palm oil (PO) at concentrations of 1-99% v/v. Classification of P.hypopthalmus oil, PO and CO were performed by the principal component analysis (PCA) and thequantification analysis was carried out by partial least square (PLS). Based on the optimization process, thebest classification results were obtained using the first derivative spectra at wave numbers of 1400-1100 cm-1.The prediction of percentage adulterated oil by PLS method also showed very good values of R2 greater than0.9999 and low standard error values in the range of 0.0176-0.703. The prediction was also perform at1400-1100 cm-1 wavenumbers using the first derivative spectra.